2016
DOI: 10.1021/acsomega.6b00229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA Methylation at the MLH1 Promoter Region Using Pyrrole–Imidazole Polyamide

Abstract: Aberrant DNA methylation causes major epigenetic changes and has been implicated in cancer following the inactivation of tumor suppressor genes by hypermethylation of promoter CpG islands. Although methylated DNA regions can be randomly demethylated by 5-azacytidine and 5-aza-2′-deoxycytidine, site-specific inhibition of DNA methylation, for example, in the promoter region of a specific gene, has yet to be technically achieved. Hairpin pyrrole (Py)–imidazole (Im) polyamides are small molecules that can be desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Py-Im polyamides have affinities for specific DNA sequences as strong as transcription factors, and these molecules can interfere with the binding of transcription factors to their recognition sites [ 26 , 29 , 31 ]. Applying the principles of these studies, we and Dervan's group recently demonstrated that Py-Im polyamides recognizing DNA with CpG sequences inhibited the induction of DNA methylation in vitro and in cellulo [ 35 , 36 ]. While these studies showed that Py-Im polyamides could be utilized to inhibit DNA methylation in a region-selective manner, the present study suggested that Py-Im polyamides could be also utilized for region-selective alteration of histone modification by conjugation with epigenetic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Py-Im polyamides have affinities for specific DNA sequences as strong as transcription factors, and these molecules can interfere with the binding of transcription factors to their recognition sites [ 26 , 29 , 31 ]. Applying the principles of these studies, we and Dervan's group recently demonstrated that Py-Im polyamides recognizing DNA with CpG sequences inhibited the induction of DNA methylation in vitro and in cellulo [ 35 , 36 ]. While these studies showed that Py-Im polyamides could be utilized to inhibit DNA methylation in a region-selective manner, the present study suggested that Py-Im polyamides could be also utilized for region-selective alteration of histone modification by conjugation with epigenetic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Sugiyama and colleagues conjugated a library of Py-Im polyamides with HDAC inhibitors or histone acetyl transferase activators and reported that each conjugate shows histone acetylation and gene activation in living cells in a different group of genes [ 37 39 ]. Because these conjugates are small molecules, they can easily be taken up through the cell membrane and localized to the nuclei [ 28 , 36 , 40 ]. In these previous reports, however, the link between epigenetically altered regions and sequences recognized by each Py-Im polyamide was not necessarily clear.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes are potentially reversible, and many drugs, such as DNA methyltransferase inhibitors, have been developed that target these changes. Unfortunately, there have been disappointing results in clinical trials, probably due to the complexity of the mechanisms underlying epigenetic change [4]. As knowledge of cancer biology improves new drug targets are being identified and developed to provide more personalized treatments.…”
Section: Basic Genomicsmentioning
confidence: 99%
“…In the past decade, a handful of small molecules have accessed and targeted the nucleosomal DNA successfully. , Particularly, the sequence-specific DNA binders are examples: pyrrole-imidazole polyamides interact with the nucleosome , and can control epigenetic processes . Apart from inhibition of DNA methylation which causes major epigenetic changes, polyamide hairpins have been used as nucleosomal clamps connecting two aligned minor grooves. They have further been used as cyanine dye–polyamide conjugates in fluorescence studies, such as Förster resonance energy transfer (FRET) on the nucleosome .…”
Section: Context and Motivationmentioning
confidence: 99%